Guanxi - "Buderi, Robert" (New York, 2006)
Recounts the lesser-known story about Microsoft and China's partnership in computer research and development, tracing the creation of Microsoft's Beijing lab, the facility's design of a more interactive and entertaining line of computers, and its role in driving the company's global business.
Keywords: Microsoft corporation-Management-Case studies